Regulation of LPS-Induced Inflammatory Responses in Bovine Mammary Epithelial Cells via TLR4-Mediated NF-κB and MAPK Signaling Pathways by Lactoferrin - Kai Zhang; Ruizhen Zhang; Yuanyuan Zhang; Min Zhang; Hong Su; Feifei Zhao; Daqing Wang; Guifang Cao; Yong Zhang (Life)
Lactoferrin (LF), a member of the transferrin family, is widely present in mammalian milk and other secretions, exhibiting anti-inflammatory, antibacterial, and anti-infective properties. Although the biological functions of LF have been extensively studied, there are few reports on its effects and molecular mechanisms concerning bovine mastitis caused by bacterial infection. This study used bovine mammary epithelial cells (BMECs) cultured in vitro as the research model. An inflammatory injury model was established by stimulating BMECs with LPS to investigate whether LF at different concentrations (10, 50, 100, and 200 μg·mL−1) could inhibit the inflammatory response before and after the onset of inflammation. The expression of inflammatory cytokines IL-1β, IL-6, IL-8, and TNF-α at both the gene and protein levels was detected using RT-qPCR and ELISA. Western blotting was employed to evaluate the phosphorylation levels in the inflammatory signaling pathways MAPK/P38/ERK and NF-κB/P65, while RT-qPCR was used to examine the impact on TLR4 receptor gene expression. The results display that pretreatment with LF prior to LPS-induced inflammation in BMECs reduced the expression of inflammatory cytokines IL-1β, IL-6, IL-8, and TNF-α at both the gene and protein levels (p < 0.05). LF also inhibited the phosphorylation of NF-κB/P65 and MAPK/P38/ERK signaling pathways and downregulated TLR4 receptor gene expression (p < 0.05). However, when LF was added after the onset of LPS-induced inflammation, inflammatory cytokine expression and phosphorylation levels in the NF-κB/P65 and MAPK/P38/ERK pathways remained elevated, along with high expression of the TLR4 receptor gene (p < 0.05). These findings show that LF can antagonize LPS-induced inflammatory responses in BMECs and reduce cytokine expression, exhibiting anti-inflammatory effects when administered before inflammation. Conversely, when LF is added post-inflammation, it appears to enhance cytokine expression, potentially promoting the recruitment of more cells or factors to resolve inflammation rapidly. Both effects are mediated through the TLR4 receptor and the NF-κB/P65 and MAPK/P38/ERK signaling pathways.